2012
DOI: 10.1117/12.908381
|View full text |Cite
|
Sign up to set email alerts
|

Live cardiomyocyte imaging via hybrid TPEF-SHG microscopy

Abstract: Utilizing a custom-built, on-stage incubator-combined, two-photon excitation fluorescence (TPEF) and second harmonic generation (SHG) imaging system, we observed new-sarcomere addition in rat neonatal cardiomyocytes during 10 hours of on-stage incubation. This addition occurred at one end of an existing myofibril, the sides of existing myofibrils, and at the interstice of several separated myofibrils; in the cases of the latter two, we observed mature myofibrils acting as templates. We found that during sarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Common examples of SHG active molecules, known as harmonophores are collagen types I and III, myosin (when present within acto-myosin complexes), and cholesterol crystals (ChC) which are chiral in nature. [8,9,10] Studies conducted by Su et al [11] have shown that extracellular matrix (ECM) alterations are a very important indicator for different kinds of tumour growth within corneal, colonic, cardiac, breast, and ovarian tissues. Intensity based SHG imaging can yield clear images of the modifications of the tissue structure, by elucidating collagen orientation changes in the ECM, as can be seen in Figure 3, which is an image taken of a sub-dermal tumour in a mouse, from the studies conducted by Brown.…”
Section: Introductionmentioning
confidence: 99%
“…Common examples of SHG active molecules, known as harmonophores are collagen types I and III, myosin (when present within acto-myosin complexes), and cholesterol crystals (ChC) which are chiral in nature. [8,9,10] Studies conducted by Su et al [11] have shown that extracellular matrix (ECM) alterations are a very important indicator for different kinds of tumour growth within corneal, colonic, cardiac, breast, and ovarian tissues. Intensity based SHG imaging can yield clear images of the modifications of the tissue structure, by elucidating collagen orientation changes in the ECM, as can be seen in Figure 3, which is an image taken of a sub-dermal tumour in a mouse, from the studies conducted by Brown.…”
Section: Introductionmentioning
confidence: 99%